2017
DOI: 10.1007/s10342-017-1027-6
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of modern forest management and clear-cutting in Sweden: Ridö State Forest 1832–2014

Abstract: The effects of clear-cutting and potential alternatives continue to be hot topics during discussions of forestry and nature conservation. This study presents forest data from Ridön, an island in Lake Mälaren in central Sweden, where forest management and clear-cutting have been applied for almost 200 years. The main objective of the study was to identify changes in forest management and forest conditions over time. The forest transition in Sweden during the 1800s is also covered, and the importance of early fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, Norway spruce started to acquire more economic value in the 1890s, which then swayed some of the previous advocates (Holmgren 1959;Granström 1991). Additionally, clear-cutting was experimented with as early as the 1880s in some parts of Sweden, under the influence of German forestry (Lundmark et al 2017), and began to be applied more widely in the early 1910s. It was supposed to be sufficient to ensure good conditions for forest regeneration and sustainable production (Holmgren 1959;Lundmark et al 2017).…”
Section: Regenerating the Boreal Forestmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Norway spruce started to acquire more economic value in the 1890s, which then swayed some of the previous advocates (Holmgren 1959;Granström 1991). Additionally, clear-cutting was experimented with as early as the 1880s in some parts of Sweden, under the influence of German forestry (Lundmark et al 2017), and began to be applied more widely in the early 1910s. It was supposed to be sufficient to ensure good conditions for forest regeneration and sustainable production (Holmgren 1959;Lundmark et al 2017).…”
Section: Regenerating the Boreal Forestmentioning
confidence: 99%
“…Additionally, clear-cutting was experimented with as early as the 1880s in some parts of Sweden, under the influence of German forestry (Lundmark et al 2017), and began to be applied more widely in the early 1910s. It was supposed to be sufficient to ensure good conditions for forest regeneration and sustainable production (Holmgren 1959;Lundmark et al 2017). In the early 1900s, burning began to be seen as a superfluous operation with no significant effect on regeneration.…”
Section: Regenerating the Boreal Forestmentioning
confidence: 99%
“…The following measures are often preferred: improved regeneration material (seedlings), fertilization, selection of sitespecific regeneration methods, different intensities of intermediate cuttings, etc. [6][7][8]. The optimal environmental conditions, appropriate silvicultural techniques and harvesting regime provide the basis for the growth of good quality wood [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, energy plantations with short cutting times are grown on an area of 1.200 ha for heat and electricity production. Whereas in 1984, about 14% of the energy produced in Sweden was derived from the dendro-mass, it was planned to increase this figure to 61% by 2015 [6]. The assessment and comparison results of the regional capacity in Northern Europe to cultivate fast-growing woody biomass showed that the potential for biomass productivity in fast-growing forest plantations is 58.5 million cubic meters per year [7].…”
Section: Introductionmentioning
confidence: 99%